The Convergence of Hyperscale Data Center and High-Performance Computing Networks. - Hoefler, Torsten; Hendel, Ariel; Roweth, Duncan (Computer (00189162), 2022)
We discuss the differences and commonalities between network technologies used in supercomputers and data centers and outline a path to convergence at multiple layers. We predict that emerging smart networking solutions will accelerate that convergence.